An analysis of hope as a contributor to local people's perspectives of tourism development. Issue 3 (2nd July 2020) - Ukaegbu, Maureen Ogechi; Carr, Neil
ABSTRACT: Hope has been understudied in the tourism literature. This paper investigates the hopes of local people through tourism development via cultural revitalization. During this qualitative research in Benin, Nigeria, community members, heritage managers, and local government employees were interviewed. Analysis of the data reveals strong advocates of cultural revitalization, cautious supporters of cultural revitalization, and conservatives as the social representations. The concept of hope, the dreams, and needs of the people in relation to tourism development were common to all three groups. Hence, it is important to consider people's hopes about tourism from the onset, because, the way people perceive tourism as a source of hope will likely have implications for how they will manage any idea about tourism development.